Non-operative treatment strategy for appendiceal abscess in children under 3 years old: a retrospective observational study - Li, Huan; Luo, Jianfeng; Wang, Haibin; Guo, Qin; Huang, Peng; Lei, Haiyan; Li, Wenhai; Yang, Jun (Frontiers in Pediatrics, 2023)
Background: There are few studies on appendiceal abscess with appendicolith in children under 3 years old. The purpose of this study is to explore the success rate of non-surgical treatment of appendiceal abscess and assess the potential influence of an appendicolith on non-surgical treatment outcomes in children under 3 years old.The clinical data of children under 3 years old diagnosed with appendiceal abscess at Wuhan Children's Hospital, China, from February 2013 to May 2020 were collected. According to the findings of ultrasound and CT imaging, they were divided into two groups: appendicolith group and non-appendicolith group.Results:94 children with appendiceal abscess were identified, meeting the specified study criteria and categorized into two groups: the appendicolith group (n=51， 54.3%) and the non-appendicolith group (n=43 ， 45.7%). Among these 94 children, non-surgical treatment was unsuccessful in 6 cases, yielding an overall success rate of 93.6% for non-surgical management of appendiceal abscess in children below the age of three. The success rate for non-surgical treatment in the appendicolith subgroup was 90.2%, while that for the non-appendicolith subgroup was 97.7%. No statistically significant distinction was observed between the two groups (P=0.292). Likewise, there were no significant differences in gender, age, duration of symptoms, fever, -2 -vomiting, diarrhea, rebound pain, WBC count, C-reactive protein level, and abscess cross-sectional area between appendicolith group and non-appendicolith group.However, there is a statistical difference in tenderness in the right lower abdomen.Non-surgical treatment of appendiceal abscess has a high success rate and can be considered as an effective treatment strategy. In pediatric patients under 3 years of age without evidence of complete intestinal obstruction or diffuse peritonitis, non-surgical treatment may be considered for appendiceal abscess.